2015
DOI: 10.1016/j.algal.2015.05.022
|View full text |Cite
|
Sign up to set email alerts
|

pH-shift processing of Nannochloropsis oculata microalgal biomass to obtain a protein-enriched food or feed ingredient

Abstract: Keywords:Microalgae Nannochloropsis Food Acid/alkaline solubilization and precipitation Protein n-3 fatty acids Fractionation of plant and animal raw materials by pH-shift processing has been widely applied to purify proteins. The principle is to solubilize proteins at high or low pH, removing debris and precipitating the proteins near their isoelectric point. We here describe the pH-shift process on commercially available Nannochloropsis oculata. The partitioning of major nutrients into the various fractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 33 publications
3
36
0
1
Order By: Relevance
“…This can be explained by the elevated cost of the purification processes, which makes it attractive only to high value products for the food, cosmetic and pharmaceutical sector (Eppink et al, 2017). The typical processes reported for algae are ultrafiltration (Safi et al, 2014b;Ursu et al, 2014), pH-shift (Cavonius et al, 2015), aqueous two-phase partitioning (Jordan and Vilter, 1991), chromatography, dialysis (Schwenzfeier et al, 2011), three phase partitioning (Waghmare et al, 2016) and…”
Section: Algae Biorefinerymentioning
confidence: 99%
See 4 more Smart Citations
“…This can be explained by the elevated cost of the purification processes, which makes it attractive only to high value products for the food, cosmetic and pharmaceutical sector (Eppink et al, 2017). The typical processes reported for algae are ultrafiltration (Safi et al, 2014b;Ursu et al, 2014), pH-shift (Cavonius et al, 2015), aqueous two-phase partitioning (Jordan and Vilter, 1991), chromatography, dialysis (Schwenzfeier et al, 2011), three phase partitioning (Waghmare et al, 2016) and…”
Section: Algae Biorefinerymentioning
confidence: 99%
“…In other words, higher yields can be achieved at expenses of low purities. Cavonius et al, (2015) and Ba et al, (2016) reported a process of high pressure homogenization and pH-shifting which resulted in protein yields of 68 to 84 % with purities of 26-44 % (DW). On the contrary, high purities can be obtained by implementing several unit operations, but having as consequence low yields.…”
Section: Techno-functional Propertiesmentioning
confidence: 99%
See 3 more Smart Citations